Consensus or Conflict? China and Globalization in the 21st Century - Wang, Huiyao; Michie, Alistair (China and Globalization,, 2021)
This open access book brings together leading international scholars and policy-makers to explore the challenges and dilemmas of globalization and governance in an era increasingly defined by economic crises, widespread populism, retreating internationalism, and a looming cold war between the United States and China. It provides the diversity of views on those widely concerned topics such as global governance, climate change, global health, migration, S&T revolution, financial market, and sustainable development. .